LKPD BERBASIS ASSURE BERPENDEKATAN STEM UNTUK MENINGKATKAN BERPIKIR KRITIS PADA MATERI ENERGI TERBARUKAN - Yulianti, Dwi; Muslifah, Zuliana Lukhi (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2026)
This study aimed to develop an ASSURE-based STEM-oriented Student Worksheet on renewable energy and to examine its validity, readability, and effectiveness in improving students' critical thinking skills. The study employed a Research and Development (R&D) method using the ADDIE development model and a quasi-experimental nonequivalent control group design. Product validity was evaluated through expert validation, readability was assessed using a cloze test, and effectiveness was determined by analyzing the improvement in students' critical thinking skills based on pretest and posttest results. The developed student worksheet demonstrated very high validity (Aiken's V = 0.93) and high readability (97%). Its implementation significantly improved students' critical thinking skills, as reflected by a higher N-Gain in the experimental group (0.72) than in the control group (0.55), with the Independent Samples t-test confirming a significant difference between the two groups (p < 0.05). This study introduces an ASSURE-based STEM-oriented student worksheet on renewable energy to improve students' critical thinking skills. Overall, the developed student worksheet was highly valid, easy to understand, and effective in enhancing students' critical thinking skills. Therefore, it has the potential to support the implementation of student-centered physics learning.